Purification and characterization of mRNA cap-binding protein from Drosophila melanogaster embryos. - Maroto, F G (1989)
A protein with specific affinity for the mRNA cap structure was purified both from the postribosomal supernatant and from the ribosomal high-salt wash of Drosophila melanogaster embryos by m7GTP-Sepharose chromatography. This protein had an apparent molecular mass of 35 kilodaltons (kDa) in sodium dodecyl sulfate-polyacrylamide gel electrophoresis, a size very different from those of the cap-binding proteins that have been characterized thus far. Drosophila 35-kDa cap-binding protein (CBP) could also be isolated from the ribosomal high-salt wash as part of a salt-stable protein complex consisting of polypeptides of 35, 72, and 140 to 180 kDa. Polyclonal antibodies against Drosophila 35-kDa CBP neither reacted with eucaryotic initiation factor 4E from rabbit reticulocytes nor affected mRNA translation in a rabbit reticulocyte cell-free system. However, in a cell-free system from Drosophila embryos, mRNA translation was specifically inhibited by these antibodies. The requirement of 35-kDa CBP for mRNA translation in Drosophila was diminished under ionic conditions in which the importance of mRNA cap structure recognition was reduced. Despite the structural differences between Drosophila 35-kDa CBP and mammalian initiation factor 4E, both proteins were functionally interchangeable in the in vitro translation system from Drosophila embryos.